The National Gallery of Scotland : An Architectural and Decorative History - Gow, Ian; Clifford, Timothy; The National Gallery of Scotland, Edinburgh (Edinburgh : Trustees of the National Galleries of Scotland, 1988)
This publication by Gow and Clifford marks the third stage of the present scheme of redecoration and rehanging, which is scheduled to re-open for the Edinburgh International Festival of 1988.
boek